2011
DOI: 10.1292/jvms.11-0270
|View full text |Cite
|
Sign up to set email alerts
|

Prokinetic Effect of the 5-HT4R Agonist Mosapride on Canine Gastric Motility

Abstract: ABSTRACT. We assessed prokinetic action of gastroprokinetic agent, mosapride in dogs. Open-label cross-over study. Six healthy beagles were administered single oral mosapride at doses of 0.5, 0.75, 1, and 2 mg/kg 30 min prior to feeding, followed by 1-week interval. The motility index (MI) of gastric contraction was ultrasonographically evaluated by change rate of antral area and contraction number. Significant increases in MI were observed at doses of 0.75 mg/kg (mean  SEM, 11.11  0.19), 1 mg/kg (11.65  0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Similarly, good correlation between the sonographic MI and GE assessed by the 13 C‐octanoic acid breath test has been reported in dogs . The sonographic assessment of the MI has been used to assess the effects of antiemetic drugs on antral motility and GE as well as the effects of various prokinetics in healthy dogs . The results of this study support the potential usefulness of the MI to assess the effects of pharmacologic agents on antral motility and GE in cats.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, good correlation between the sonographic MI and GE assessed by the 13 C‐octanoic acid breath test has been reported in dogs . The sonographic assessment of the MI has been used to assess the effects of antiemetic drugs on antral motility and GE as well as the effects of various prokinetics in healthy dogs . The results of this study support the potential usefulness of the MI to assess the effects of pharmacologic agents on antral motility and GE in cats.…”
Section: Discussionsupporting
confidence: 74%
“…Since cisapride was withdrawn from the market for its cardiac arrhythmia side effect, mosapride has been used as a prokinetic agent for the treatment of dyspeptic symptoms of gastrointestinal disorders such as chronic gastritis, functional dyspepsia, irritable bowel syndrome, and gastric esophageal reflux disease [5,17]. Mosapride also enhances upper gastrointestinal motility in dogs [29,33] and has been approved as a prokinetic agent for canines in Japan. We have previously demonstrated that mosapride is effective for treating vincristine-induced gastric motility disorder in dogs [28].…”
mentioning
confidence: 99%
“…Mosapride is a novel 5‐HT 4 receptor agonist that enhances GI motility. It is used as a prokinetic in people and has recently been evaluated for use in dogs . Tegaserod, a potent partial 5‐HT 4 agonist and a weak 5‐HT 1D receptor agonist, has been shown to increase antral, duodenal, jejunal, and colonic motility in conscious dogs .…”
Section: Specific Pharmacological Interventionsmentioning
confidence: 99%